An investigation into the correlation between intraperitoneal teicoplanin concentrations and treatment outcomes in peritoneal dialysis-associated peritonitis - Lulu Wang; Lulu Wang; Jiangqing Fan; Xuejie Chen; Wenpu Lei; Chunming Jiang; Hang Liu; Yun Yang; Jizhong Shen (Frontiers Media S.A., 2024)
Peritoneal dialysis-associated peritonitis (PDAP) is a frequent complication of peritoneal dialysis. The guidelines from the International Society for Peritoneal Dialysis (ISPD) suggest administering teicoplanin through the peritoneal route to treat PDAP, but do not specify the ideal concentration for peritoneal dialysis effluent (PDE). Patients meeting the trial criteria for PDAP in our hospital between July 2022 and December 2023 were enrolled. Data on PDE white blood cell count, PDE neutrophil percentage, clinical symptoms, CRP, and PCT were gathered pre- and post-treatment. Incidences of adverse drug reaction (ADR) and case numbers during treatment were recorded. Subsequently, patients were categorized into cured and uncured groups for evaluating the relationship between PDE teicoplanin concentration and treatment effectiveness. The self-control study results on teicoplanin efficacy indicated intraperitoneal teicoplanin administration achieved an efficacy rate of 88.9% and an ADR incidence of 5.5% in treating PDAP patients. There was no observed correlation between teicoplanin blood concentration and PDE concentration. PDE teicoplanin concentrations on days 1, 3, 5, and 7 post-dosing were higher inthe cured group, with a significant contrast in PDE concentration on day 5 between the 18.98 ± 2.43 mg/L of the cured group and the 12.07 ± 2.68 mg/L of the uncured group. ROC curve revealed a higher likelihood of cure in patients when PDE teicoplanin concentration exceeded 15.138 mg/L on day 5 post-dosing. Univariate and multifactorial studies identified 24-h urine volume and the number of daily abdominal dialysis sessions as influential factors in PDE teicoplanin concentration on day 5. A positive correlation was found between 24-h urine volume and PDE teicoplanin concentration, with PDAP patients having urine volume over 537 mL showing significantly higher drug concentrations. Conversely, the number of daily PDAP sessions was negatively correlated with PDE teicoplanin concentrations, indicating that patients with 1∼3 daily PDAP sessions had notably higher PDE teicoplanin concentrations compared to those with 4∼6 sessions. Therefore, PDAP patients who use intraperitoneal teicoplanin could effectively control infection by monitoring the PDE teicoplanin concentration (>15.138 mg/L) on day 5 after dosing.